Antibacterial Activity of Silver Nanoparticle and L-carnitine Advantages on Mixed Vaginitis Caused by Candida albicans/ Escherichia Coli in Mice Models: An Experimental Study: Effects of Silver Nanoparticle and L-carnitine on Mixed Vaginitis - Fatahi Dehpahni, Mozhgan; Chehri, Khosrow; Azadbakht, Mehri (Iranian Journal of Pharmaceutical Sciences, 2021)
Mix vaginitis refers to at least two potential pathogenic microbes in the vagina. Recently, the popularity of nanoparticles is increasing; these materials have been widely used as an antimicrobial agent in the treatment of chronic infections in which silver nanoparticles (AgNPs) are more widely considered. We aimed to establish a mixed vaginitis model in adult mice with Candida albicans and Escherichia coli, then evaluated the effect of AgNPs and L. carnitine (LC) to treat the vaginitis. In our study, the microdilution method and minimum biofilm inhibitory concentration were used for the antimicrobial activity of AgNPs. Vaginitis was made by intra-vaginal inoculation of 107 CFU/ml of both E. coli/C. albicans in adult NMRI mice. Mice were classified into 8 groups: (1) healthy mice without any treatment, (2) mice were infected intravaginally with equal volumes of C. albicans and E. coli suspensions, (3) healthy mice that received daily intraperitoneal injection of 250 mg/kg LC for two weeks, (4) infected mice that treated with a daily injection of 250 mg/kg LC for two weeks, (5) healthy mice that received daily intravaginal inoculation of 250 ppm of AgNPs for two weeks, (6) infected mice treated with daily intravaginal inoculation of 250 ppm AgNPs for two weeks, (7) healthy mice that received daily intravaginal inoculation of 250 ppm AgNPs and a daily injection of 250 mg/kg LC for two weeks, and (8) mice treated with daily intravaginal inoculation of 250 ppm AgNPs and a daily injection of 250 mg/kg LC for two weeks. All treatments with AgNPs and LC were daily for two weeks. A vaginal smear was taken throughout the experiment, and tissue sections were prepared using the hematoxylin-eosin method. The results showed that the 50% inhibitory concentration (IC-50) of AgNPs for E. coli, C. albicans, and their mixture was 96.84, 11.23, and 35.67 ppm, respectively, and their IC- 90 values were 201.77, 105.51, and 173.13 ppm, respectively. MBIC-90 % of AgNPs for E. coli, C. albicans, and the mixture of them were 500, 125, and 250 ppm, respectively. The estrus cycle in treated mice was similar to intact mice, and the order of their vaginal tissue sections confirmed the treatment of mixed vaginitis. In conclusion, co-administration of AgNPs and LC may eliminate the adverse effect of AgNPs and mixed vaginitis.